PEMBELAJARAN DALAM JARINGAN BAGI MAHASISWA PENDIDIKAN MATEMATIKA - Mandur, Kanisius; Nendi, Fransiskus; Efrem Men, Fulgensius; Jelatu, Silfanus (Jurnal Pendidikan dan Kebudayaan Missio, 2022)
The goal of this study was to ascertain how students in mathematics education reacted to online instruction. This study employs a quantitative evaluation framework. The Systematic Random Sampling approach was used to choose the 120 respondents, all of whom are students in mathematics. Through an online survey completed utilizing a Google form, the study's data collection process involves gathering student feedback on online learning. Quantitative descriptive analysis was used to examine the data. The findings revealed that the first category, student motivation for online learning, was in the poor range, followed by the poor range for the Moodle-provided teaching materials, the fairly good range for the implementation of online learning, the fairly good range for the evaluation, and the good range for the challenges encountered during online learning. Therefore, in general, students studying mathematics education do not favor online learning.